Evaluation of the interaction of diosgenin and its derivatives with cyclodextrin to form a water-soluble inclusion complex: A molecular docking study - Rismawanti, Rusi; Asnawi, Aiyi; Muttaqin, Fauzan Zein (Science Midwifery, 2024)
Diosgenin as an herbal compound has been shown to have activity as an atherosclerosis agent, but the low solubility of the compound may hinder the research process of diosgenin as a medicinal substance. This study aimed to examine the interaction and affinity of diosgenin compounds and their derivatives with the macromolecule cyclodextrin to increase solubility by inclusion complex formation. Alpha and beta cyclodextrins and all ligands were optimized using the density functional theory (DFT) method and the 6-31G base set with hybrid functional B3LYP. Next, molecular docking was carried out using AutoDock. Of the 12 compounds that were tethered to each macromolecule, the compound 2-chloro-3-(((4S,5'R,6aR,6bS,8aS,8bR,9S,10R,11aS,12aS,12bS)-5',6a,8a,9- tetramethyl-1,3,3',4,4',5,5',6,6a,6b,6',7,8,8a,8b,9,11a,12,12a,12b-icosahydrospiro[naphtho[2',1':4,5]indeno[2,1-b]furan-10,2'-pyran]-4-yl)oxy)naphthalene-1,4-dione (M18) and the α-cyclodextrins were found to have the lowest binding free energy (∆G) and inhibition constant (Ki) of -6.42 kcal/mol and 19.80 uM, respectively. The results of this study can be studied and continued as future research material to develop evidence of increasing solubility in compounds by forming inclusion complexes with macromolecules. In conclusion, diosgenin and cyclodextrin macromolecules interact to form a water-soluble inclusion complex.